Once upon two cities a parallel between New York City and Bucharest by 1900 - Neţ, Mariana 1956- (CompLit InterArts book series, 2016)
"This book is an excursion into the past. It deals with two cities: New York and Bucharest in the era between 1865 and 1914. The two cities are representative of the two countries they belong to, but they are also important in themselves, qua cities. This is the era when both cities were being built and began to assert their identities, when they were becoming aware of their assets and starting to talk about them"...Preface